Positive electrode active material and preparation method thereof
By using LixMOyClz clad material on the surface of the positive electrode particles of the lithium-ion power battery, the problem of poor interface contact caused by reaction of high-nickel ternary materials and water is solved, and higher energy density and cycling stability are achieved, and production costs are reduced.
Patent Information
- Application Number
- CN202411348672.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-03-14
AI Technical Summary
When the prior art improves the energy density and cycle stability of lithium-ion power batteries, it faces the problem of poor interface contact caused by reaction between high-nickel ternary materials and water, and the coating method is complex and costly.
LixMOyClz is used as the cladding material, and by coating it on the surface of the positive electrode particles in a non-aqueous solvent, an electrolyte cladding layer is formed, which reduces the interface resistance and increases the lithium ion conductivity.
Effectively reduces interface impedance, improves lithium ion conductivity and cycling stability, and can match higher voltage active materials, suitable for coating of water-sensitive materials.
Smart Images

Figure CN119627062A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a positive electrode active material and a preparation method thereof. Background Art
[0002] With the booming development of the new energy vehicle industry, the research on lithium-ion power batteries has progressed rapidly. Liquid lithium-ion batteries use organic solvents as electrolytes, which can bring safety hazards such as liquid leakage, fire and explosion. Solid-state batteries do not contain electrolytes, so they can avoid dangers such as fire and leakage. At the same time, they can achieve higher energy density than liquid batteries. They are a promising development direction. The core lies in using completely solid electrolyte materials to replace existing electrolytes. At present, the ionic conductivity of solid electrolyte materials is still far from that of electrolytes. The most important thing is that the solid-solid interface between the electrode and the electrolyte has poor contact after losing the infiltration of the electrolyte, which easily produces a large interface impedance and affects the performance of the battery.
[0003] In order to improve the interface contact, the commonly used methods include mixing a small amount of oxide electrolyte particles into the positive electrode material, or constructing an oxide electrolyte coating layer on the surface of the positive electrode particles. With the gradual development of inorganic solid electrolyte systems, research on halide solid electrolytes has also continued to deepen, and a modification method using halide-coated electrode materials has emerged to achieve the purpose of reducing the interface impedance between the electrode and the solid electrolyte. Most of the halide coatings currently used are limited to Li3InCl6. Since the raw materials are easily soluble in water, the electrolyte can be precipitated on the surface of the positive electrode particles by evaporating the solvent to achieve interface modification. For example, in the prior art, Chinese invention patent application CN111509293A discloses a method for reducing the grain boundary impedance and interface impedance of oxide electrolytes, wherein the coating material Li3InCl6 is dissolved in a mixed solvent of ethanol-water, and mixed with the electrode material lithium cobalt oxide and the conductive agent acetylene black, and the Li3InCl6 is attached to the surface of the positive electrode particles by removing the solvent and calcining, and the interface contact between the treated positive electrode sheet and the LLZO oxide electrolyte sheet is significantly improved, and the cycle stability of the assembled battery is improved, and the water-based coating method is used to coat it on the surface of the lithium cobalt oxide positive electrode. However, with the increasing demand for the energy density of lithium-ion power batteries, positive electrode materials are also developing towards high-nickel ternary positive electrodes, and high-nickel ternary materials are easy to react with water, generating byproducts on the particle surface that affect lithium ion transport, so this method cannot achieve the desired effect of improving the interface contact between the electrode and the electrolyte when applied to high-nickel ternary materials. In order to solve the impact of the water system, China's invention patent application CN116344781A discloses a method and active material for coating the surface of an electrode active material with a halide electrolyte, which is first coated on the surface of a high-nickel ternary electrode material substrate with a carbon layer for protection, then coated on the surface of the carbon layer in an aqueous phase with Li3InCl6, and finally calcined the coated material to obtain a composite electrode active material with a surface coated with a Li3InCl6 halide electrolyte, thereby avoiding the high-nickel ternary electrode particles from reacting with water and affecting performance, and better playing the role of the coating layer in improving interface contact. This solution adopts a two-step coating method. In addition to the relatively complex synthesis steps, it is also necessary to remove the carbon layer coated in the first step by calcining at a higher temperature after coating, which is relatively costly and not conducive to large-scale production. Summary of the invention
[0004] The present application provides a positive electrode active material and a preparation method thereof, which uses Li x MO y Cl z As a coating layer material, it can match the active material body with a higher voltage, and can be coated in a non-aqueous solvent, thereby achieving the coating of the active material body that is sensitive to water.
[0005] In a first aspect, the present application provides a positive electrode active material, the positive electrode active material comprising an active material body and an electrolyte coating layer, the electrolyte coating layer is coated on the surface of the active material body, and the material of the electrolyte coating layer comprises Li x MO y Cl z , wherein M includes at least one of Y, Al, Zr, Hf, Nb and Ta, 1≤x / y≤4, 1≤z / y≤8.
[0006] As an optional embodiment, the mass ratio of the electrolyte coating layer to the active material body is 1:
[0007] (2~30).
[0008] As an optional embodiment, the active material body includes at least one of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide and lithium-rich manganese-based materials.
[0009] As an optional implementation, the particle size of the active material body is 1 μm to 30 μm.
[0010] In a second aspect, the present application provides a method for preparing a positive electrode active material, the method comprising:
[0011] Get Li x MO y Cl z , wherein M includes at least one of Y, Al, Zr, Hf, Nb and Ta, 1≤x / y≤4, 1≤z / y≤8;
[0012] The active material bulk and the Li x MO y Cl z dissolving in a second solvent to obtain an active material solution;
[0013] The active material solution is evaporated and heat treated to convert the Li x MO y Cl z The electrolyte coating layer is coated on the surface of the active material body to obtain a positive electrode active material.
[0014] As an optional embodiment, the Li x MO y Cl z include:
[0015] The reaction raw materials are dissolved in a first solvent to carry out a chemical reaction to obtain Li x MO y Clz ; wherein the reaction raw materials include at least one of Li2O, LiOH, LiCl, YCl3, AlCl3, ZrCl4, HfCl4, NbCl5 and TaCl5.
[0016] As an optional implementation manner, the mass ratio of the reaction raw material to the first solvent is 1:(5-1000).
[0017] As an optional embodiment, the first solvent is the same as the second solvent; and / or
[0018] The first solvent comprises at least one of water, ethanol, isopropanol, methanol and n-butanol; and / or
[0019] The second solvent includes at least one of water, ethanol, isopropanol, methanol and n-butanol.
[0020] As an optional embodiment, the second solvent does not contain water.
[0021] As an optional implementation manner, the evaporation temperature is 20°C to 120°C.
[0022] As an optional implementation manner, the temperature of the heat treatment is 100° C. to 300° C.; the time of the heat treatment is 4 h to 20 h.
[0023] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0024] The positive electrode active material provided in the embodiment of the present application adopts Li x MO y Cl z As a coating material, it has a very high ionic conductivity. Coating it on the surface of the positive electrode particles can effectively reduce the interface resistance, improve the overall lithium ion conductivity, and improve the cycle stability. At the same time, due to the introduction of the O element, it can match the active material body with a higher voltage. And it can be coated in non-aqueous solvents, thereby achieving the coating of water-sensitive active material bodies. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0026] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0027] Figure 1 A flowchart of the method provided in the embodiment of the present application. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0029] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0030] The present invention provides a positive electrode active material, wherein the positive electrode active material comprises an active material body and an electrolyte coating layer, wherein the electrolyte coating layer is coated on the active material body, and the material of the electrolyte coating layer comprises Li x MO y Cl z , wherein M includes at least one of Y, Al, Zr, Hf, Nb and Ta, 1≤x / y≤4, 1≤z / y≤8.
[0031] The positive electrode active material is Li x MO y Cl z As a coating material, it has high ionic conductivity. It is coated on the surface of the positive electrode particles using a liquid phase method. The electrode material will be more closely connected with the oxide and halide solid electrolyte, thereby effectively reducing the interface resistance, improving the overall lithium ion conductivity, and improving the cycle stability. At the same time, due to the introduction of the O element, it can match the active material with a higher voltage. And it can be coated in non-aqueous solvents, thereby achieving the coating of water-sensitive active materials.
[0032] Li x MO y Cl zSpecifically, it can be Li2AlOCl3, Li2ZrOCl4, etc. Among them, the preparation process of Li2AlOCl3 can be: weighing 2.643g LiOH and 7.357g AlCl3 in a glove box, putting them in an agate mortar, manually grinding and mixing for 10 minutes, transferring the mixed powder to a zirconia ball mill, adding 120g 5mm zirconia grinding balls, adding a stainless steel sleeve and sealing it, then taking out the glove box, using a planetary ball mill at a speed of 150rpm for 1h, and then at a speed of 600rpm for 48h to obtain Li2AlOCl3 powder; the preparation process of Li2ZrOCl4 can be: weighing 1.705g LiOH and 8.295g in a glove box. ZrCl4 was put into an agate mortar and manually ground and mixed for 10 min. The mixed powder was transferred to a zirconia ball mill, 120 g of 5 mm zirconia grinding balls were added, a stainless steel sleeve was installed and sealed, and then taken out of the glove box. A planetary ball mill was used for ball milling at a speed of 150 rpm for 1 h, and then at a speed of 600 rpm for 48 h to obtain Li2ZrOCl4 powder.
[0033] In some embodiments, the mass ratio of the electrolyte coating layer to the active material body is 1:(2-30).
[0034] Exemplarily, the mass ratio of the electrolyte coating layer to the active material body can be 1:2, 1:4, 1:6, 1:8, 1:10, 1:12, 1:14, 1:16, 1:18, 1:20, 1:22, 1:24, 1:26, 1:28 or 1:30, etc., and it can also be any value in the range of 1:(2~30).
[0035] In some embodiments, the active material body includes at least one of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, nickel cobalt manganese oxide and lithium-rich manganese-based materials. Among them, the nickel cobalt manganese oxide can be high nickel cobalt manganese oxide, which refers to nickel cobalt manganese oxide with a high nickel content, which can be understood as nickel cobalt manganese oxide of series 5 or above, such as 6 series nickel cobalt manganese oxide, 7 series nickel cobalt manganese oxide, 8 series nickel cobalt manganese oxide or 9 series nickel cobalt manganese oxide.
[0036] In some embodiments, the particle size of the active material body is 1 μm to 30 μm.
[0037] Exemplarily, the particle size of the active material body can be 1μm, 3μm, 5μm, 7μm, 9μm, 11μm, 13μm, 15μm, 17μm, 19μm, 21μm, 23μm, 25μm, 27μm, 29μm or 30μm, etc., and it can also be any value in the range of 1μm to 30μm.
[0038] Figure 1 A flow chart of the method provided in the embodiment of the present application is as follows: Figure 1 As shown, based on a general inventive concept, an embodiment of the present application also provides a method for preparing a positive electrode active material.
[0039] The method is used for preparing the above-mentioned positive electrode active material. The specific content of the positive electrode active material can refer to the above-mentioned embodiment. Since the method adopts part or all of the technical solutions of the above-mentioned embodiment, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be repeated here one by one.
[0040] In some embodiments, the method comprises:
[0041] S1. Get Li x MO y Cl z , wherein M includes at least one of Y, Al, Zr, Hf, Nb and Ta, 1≤x / y≤4, 1≤z / y≤8;
[0042] In some embodiments, the Li x MO y Cl z The process comprises: mixing the reaction raw materials with a first solvent, and then reacting to obtain Li x MO y Cl z ; Wherein, the reaction raw materials include at least one of Li2O, LiOH, LiCl, YCl3, AlCl3, ZrCl4, HfCl4, NbCl5 and TaCl5. Wherein, the selection of each reaction raw material can be determined according to the molar ratio of each element in the target product to be prepared, and then configured in a stoichiometric ratio.
[0043] In some embodiments, the first solvent includes at least one of water, ethanol, isopropanol, methanol, and n-butanol.
[0044] S2. The active material body and the Li x MO y Cl z Dissolved in a second solvent to obtain an active material solution.
[0045] In some embodiments, the second solvent includes at least one of water, ethanol, isopropanol, methanol, and n-butanol.
[0046] In some embodiments, the first solvent is the same as the second solvent. Further, the above S1 and S2 can be completed in one step, specifically: mixing the reaction raw materials with the solvent to obtain a mixed solution, mixing the mixed solution with the active material body, and then evaporating and heat treating to convert Li x MO y Cl zThe active material is coated to form a coating layer to obtain a positive electrode active material.
[0047] Further, the mass ratio of the reaction raw material to the first solvent is 1:(5-1000). Exemplarily, the mass ratio of the reaction raw material to the first solvent can be 1:5, 1:100, 1:200, 1:300, 1:400, 1:500, 1:600, 1:700, 1:800, 1:900 or 1:1000, etc., and can also be any value within the range of 1:(5-1000).
[0048] When the active material body is a water-sensitive material, such as high-nickel cobalt lithium manganese oxide, in some embodiments, the second solvent does not contain water.
[0049] S3. The active material solution is evaporated and heat treated to convert the Li x MO y Cl z Coated on the surface of the active material body to form an electrolyte coating layer on the surface of the active material body to obtain a positive electrode active material.
[0050] In some embodiments, the evaporation temperature is 20° C. to 120° C. Exemplarily, the evaporation temperature can be 20° C., 30° C., 40° C., 50° C., 60° C., 70° C., 80° C., 90° C., 100° C., 110° C. or 120° C., etc., and can also be any value within the range of 20° C. to 120° C.
[0051] In some embodiments, the temperature of the heat treatment is 100°C to 300°C; the time of the heat treatment is 4h to 20h. Exemplarily, the temperature of the heat treatment can be 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C or 300°C, etc., which can also be any value in the range of 100°C to 300°C. The time of the heat treatment can be 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h or 20h, etc., which can also be any value in the range of 4h to 20h.
[0052] Specifically, in this embodiment, the preparation process of the positive electrode active material can be to configure one or more of the reaction raw materials Li2O, LiOH, LiCl, YCl3, AlCl3, ZrCl4, HfCl4, NbCl5, TaCl5 into a mixed solution in a stoichiometric ratio, and the solvent can be one or more of water, ethanol, isopropanol, methanol, and n-butanol, and the mass ratio of the total mass of the reaction raw materials to the solvent is 1:1000 to 1:5. An appropriate amount of active material body particles are mixed evenly with the above solution, wherein the particle size of the active material body particles is 1 to 30 μm, and the mass ratio of the coating layer material to the active material body is 1:30 to 1:2, and the slurry is continuously stirred and the solvent is evaporated, and the evaporation solvent temperature is controlled between room temperature and 120°C. The solid particles obtained after the solvent is completely removed are heat treated under vacuum or inert gas protection at a temperature of 100°C to 300°C for 4 to 20 hours to precipitate the oxychloride and form an electrolyte membrane on the surface of the active material particles, thereby obtaining active material particles coated with oxychloride, i.e., positive electrode active materials.
[0053] The positive electrode active material can be mixed with an appropriate amount of conductive agent and binder to form an electrode slurry, and a positive electrode sheet can be prepared. When pressed with an oxide or halide solid electrolyte sheet, it can effectively reduce the interface impedance and improve the cycle characteristics of the solid-state battery.
[0054] The method has a simple process, a thin film with good uniformity, and is conducive to reducing raw material consumption and thus reducing costs. The oxychloride ions as the precipitated phase have high electrical conductivity, a low temperature during the heat treatment process, low energy consumption, and low production costs. The method can be well adapted to existing positive electrode materials and commonly used oxide and halide solid electrolyte systems, improve interfacial impedance, and enhance the electrical properties of solid-state full batteries, which is conducive to improving the performance and reducing costs of solid-state batteries.
[0055] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.
[0056] Example 1
[0057] A positive electrode active material, the preparation process of which is as follows:
[0058] The active material body uses lithium cobalt oxide with an average particle size of 3μm, the coating material is Li2AlOCl3, and the solvent uses a mixed solvent of water and ethanol in a volume ratio of 1:1. 0.5g of Li2AlOCl3 raw material is first dissolved in 50ml of solvent, stirred for more than 30min, and then 4g of lithium cobalt oxide powder is added and stirred for more than 30min. The container is transferred to a vacuum oven, set to a constant temperature of 80℃ to remove the solvent, and after about 10h, it is confirmed that the solvent has evaporated completely, and the oven temperature is increased to 180℃ and kept warm for 12h to obtain lithium cobalt oxide electrode particles with a surface uniformly coated with Li2AlOCl3 electrolyte, that is, the positive electrode active material.
[0059] Example 2
[0060] A positive electrode active material, the preparation process of which is as follows:
[0061] The active material body uses high nickel ternary material (NCM811) with an average particle size of 10μm, the coating material is Li2ZrOCl4, and the solvent is isopropanol. 0.5g of Li2ZrOCl4 raw material is first dissolved in 100ml of solvent, stirred for more than 30min, and then 5g of positive electrode powder is added and stirred for more than 30min. The container is transferred to a vacuum oven, set to a constant temperature of 100℃ to remove the solvent, and after about 10h, it is confirmed that the solvent has evaporated completely, and the oven temperature is increased to 200℃ and kept warm for 10h to obtain high nickel ternary electrode particles with Li2ZrOCl4 electrolyte uniformly coated on the surface, that is, positive electrode active materials.
[0062] Comparative Example 1
[0063] A positive electrode active material, the preparation process of which is as follows:
[0064] The active material body uses lithium cobalt oxide with an average particle size of 3μm, and the coating material is Li3InCl6. The solvent uses a mixed solvent of water and ethanol in a volume ratio of 1:2. 0.5g of Li3InCl6 raw material is first dissolved in 50ml of solvent, stirred for more than 30min, and then 2g of lithium cobalt oxide powder is added and stirred for more than 30min. The container is transferred to a vacuum oven, set to a constant temperature of 80℃ to remove the solvent, and after about 10h, it is confirmed that the solvent has evaporated completely, and the oven temperature is increased to 180℃ and kept warm for 12h to obtain lithium cobalt oxide electrode particles with a surface uniformly coated with Li3InCl6 electrolyte, that is, the positive electrode active material.
[0065] Comparative Example 2
[0066] A positive electrode active material, the preparation process of which is as follows:
[0067] The active material body uses high nickel ternary material (NCM811) with an average particle size of 10μm, the coating material is Li3InCl6, and the solvent uses a mixed solvent of water and ethanol in a volume ratio of 1:3. 0.5g of Li3InCl6 raw material is first dissolved in 100ml of solvent, stirred for more than 30min, and then 2g of positive electrode powder is added and stirred for more than 30min. The container is transferred to a vacuum oven, set to a constant temperature of 80℃ to remove the solvent, and after about 10h, it is confirmed that the solvent has evaporated completely, and the oven temperature is increased to 180℃ and kept warm for 12h to obtain Li3InCl6-high nickel ternary composite electrode particles, that is, positive active materials.
[0068] The performance of the positive electrode active materials provided in each embodiment and comparative example was tested, and the results are shown in the following table:
[0069]
[0070]
[0071] It can be seen from the above table that by using the positive electrode active material provided in the embodiment of the present application, by using Li x MO y Cl z As a coating material, it can match the active material body with higher voltage, and can be coated in non-aqueous solvents, thereby achieving the coating of active material bodies that are sensitive to water.
[0072] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0073] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present specification, the terms "including", "comprising", etc. refer to "including but not limited to". In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of the associated objects, indicating that there may be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A, B can be singular or plural. In this article, "at least one" refers to one or more, and "plural" refers to two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of singular or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can both mean: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b and c can be single or multiple.
[0074] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A positive electrode active material, characterized in that: The positive electrode active material comprises an active material body and an electrolyte coating layer, wherein the electrolyte coating layer is coated on the surface of the active material body, and the material of the electrolyte coating layer comprises Li x MO y Cl z , wherein M includes at least one of Y, Al, Zr, Hf, Nb and Ta, 1≤x / y≤4, 1≤z / y≤8.
2. The positive electrode active material according to claim 1, characterized in that The mass ratio of the electrolyte coating layer to the active material body is 1:(2-30).
3. The positive electrode active material according to claim 1, characterized in that The active material body includes at least one of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide and lithium-rich manganese-based materials.
4. The positive electrode active material according to claim 1, characterized in that The particle size of the active material body is 1 μm to 30 μm.
5. A method for preparing a positive electrode active material, characterized in that: The method comprises: Get Li x MO y Cl z , wherein M includes at least one of Y, Al, Zr, Hf, Nb and Ta, 1≤x / y≤4, 1≤z / y≤8; The active material bulk and the Li x MO y Cl z dissolving in a second solvent to obtain an active material solution; The active material solution is evaporated and heat treated to convert the Li x MO y Cl z The electrolyte coating layer is coated on the surface of the active material body to obtain a positive electrode active material.
6. The method for preparing the positive electrode active material according to claim 5, characterized in that: The obtained Li x MO y Cl z include: The reaction raw materials are dissolved in a first solvent to carry out a chemical reaction to obtain Li x MO y Cl z ; wherein the reaction raw materials include at least one of Li2O, LiOH, LiCl, YCl3, AlCl3, ZrCl4, HfCl4, NbCl5 and TaCl5.
7. The method for preparing a positive electrode active material according to claim 6, characterized in that: The mass ratio of the reaction raw material to the first solvent is 1:(5-1000).
8. The method for preparing a positive electrode active material according to claim 6, characterized in that: The first solvent is the same as the second solvent; and / or The first solvent and the second solvent respectively include at least one of water, ethanol, isopropanol, methanol and n-butanol.
9. The method for preparing a positive electrode active material according to claim 5, characterized in that: The evaporation temperature is 20°C to 120°C.
10. The method for preparing a positive electrode active material according to claim 5, characterized in that: The temperature of the heat treatment is 100° C. to 300° C., and the time of the heat treatment is 4 h to 20 h.
Citation Information
Patent Citations
Lithium iron phosphate positive electrode material, preparation method and application thereof
CN115663176A
Oxygen-containing chloride solid electrolyte and preparation method and application thereof
CN115842157A
Halide solid electrolyte and preparation method thereof
CN116960441A
Lithium manganese iron phosphate composite positive electrode material and preparation method thereof, positive electrode plate and battery
CN117117139A
Novel oxyhalide electrolyte and preparation method and application thereof
CN118117156A